PENGARUH ATRIBUT DAN KEPERCAYAAN TERHADAP NIAT BELI PRODUK MEREK INDOMIE MELALUI SIKAP (STUDI MASYARAKAT KOMPLEK TAMANGAPA) - Syamsul Alam; Nur Naninsih; Dewi Pratiwi Indriasari (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
The This study aims to analyze and understand how peopl’s purchase intention for Indomie brand products are. This study analyzes the effect of attributes and beliefs through attitudes towards purchase intentions of Indomie Brand Products. This type of research is quantitative with research samples taken from individuals who have been in the Tamangapa complex. The research instrument used a questionnaire with a total of 110 valid questionnaires collected by the researcher. Data analysis was processed using Path Analysis with SPSS software for data processing. The results of this study found that the relationship between the variables had a positive and significant effect on both the independent, dependent, and intervening variables. The theoretical implication in this study contribute that the attitude can be studied as a mediating variable.